The influence of Christianity in society: A Syriac (Aramaic) viewpoint - Issa, B.; Issa, Theodora (Nova Science Publishers, 2012)
This chapter focuses on the idea of how Christianity influenced society as a whole. Though influences are clear, nonetheless, this has been an area of immense debate, especially with Neusner (1988) contending that the academic study of religion faces enemies on two fronts: secular and theological. No matter how many scholars, theologians or philosophers are interested in this debate, and in the words of Sawyers (2002) who analyses Thomas Moore, the Soul's Religion: Cultivating a Profoundly Spiritual way of life, opines that no matter how rich and sophisticated the analysis of the spiritual malaise in the twenty-first century, Moore neither coddles the ego nor offers a fast and easy solutions to life‘s problems but instead encourages being open to mystery. Recently, Pearce (2011) in an attempt to assess the claim that an education rooted in a simple commitment to scientific progressivism will be inadequate to the demands of the 21st Century. Thus, there needs to be a solution to this dilemma. Drawing from the Holy Bible, and Syriac (Aramaic) Church‘s tradition, the influence of Christianity on society is examined in a way that is relevant to the current debates on the role of Christianity in such a dynamic and complex world, where diverse philosophies and ideologies are sweeping to takeover the traditional Christian way of life. The main aim of the chapter, deriving from the Holy Bible is to present evidence from the Holy Bible on the basis of morality and moral actions. In recent times there have been increased calls to worship ‗rationality‘ or ‗reason‘ urging individuals to abandon the traditional way of worshiping God the Almighty Our Lord Jesus Christ. Their argument is based on their inability to believe or be ‗rationally‘ convinced of the great miracles that form one of the pillars of Christian beliefs. As a result, wisdom needs to prevail.